Prognostic value of receptor activator of nuclear factor kappa-B (RANK) marker in patients with breast cancer - S. I. Zabroda; E. A. Maslyukova; L. I. Korytova; G. A. Raskin; K. M. Pozharissky; O. V. Korytov (ABV-press, 2015)
Despite notable progress made in studying breast cancer (BC), the mechanisms of metastases, in view of the classification into molecular subtypes, in patients with BC remain to be fully uninvestigated, in the presence of a good prognosis in particular. To study novel diagnostic and predictive markers in a new way presents current problems in the pathology of BC. This investigation deals with the expression of osteoprotegerin (OPG) in the tumor cells of patients with BC. It enrolled 83 patients with locally advanced BC (T2-4N0-3M0) who had been treated in 2003 to 2010. The inclusion criterion was a histologically verified diagnosis of invasive BC. To study the level of OPG, the investigators conducted an immunohistochemical study of biopsy sections according to the standard protocol. The mean expression of receptor activator of nuclear factor kappa-B (RANK) in the BC cells was 18.7 %; itsmedian was 5 % (range, 0-90 %). The patients were divided into 2 groups according to the level of RANK expression: 1) high (higher than the median); 2) low (lower than the median). The high RANK group included 39 patients; the low RANK group comprised 44 patients. Analysis of the clinical and pathological characteristics of BC patients with regard RANK expression did not show any statistically significant differences in the presence or absence of affected regional lymph nodes, T category, and Ki-67 index. The analysis of clinical and pathomorphological and immunohistochemical characteristics in patients with breast cancer, taking into consideration RANK expression level, did not show any statistically significant differences with respect to presence or absence of affected regional lymph nodes, age, T category and Ki-67 index (р > 0.05). However, it revealed the following pattern: the high expression of RANK was more common in patients positive for estrogen and progesterone receptors than in those for negative receptors (p = 0.04).